Fractional calculus: an introduction for physicists. - Herrmann, Richard; Herrmann, Richard (World Scientific Publishing Co. Pte. Ltd, 2011)
Fractional calculus is undergoing rapid and ongoing development. We can already recognize, that within its framework new concepts and strategies emerge, which lead to new challenging insights and surprising correlations between different branches of physics.